In order to learn : how the sequence of topics influences learning - Ritter, Frank E. (Oxford series on cognitive models and architectures., 2007)
The order that material, for both facts and skills, is presented or explored by a learner can strongly influence what is learned, how fast performance increases, and sometimes, even that the material is learned at all. This text argues that these effects are more pervasive and important than they have been treated.